Sex Differences in Cardiac Troponin I and T and the Prediction of Cardiovascular Events in the General Population. (8th July 2021) - Kimenai, Dorien M; Shah, Anoop S V; McAllister, David A; Lee, Kuan Ken; Tsanas, Athanasios; Meex, Steven J R; Porteous, David J; Hayward, Caroline; Campbell, Archie; Sattar, Naveed; Mills, Nicholas L; Welsh, Paul
Abstract: Background: Cardiac troponin concentrations differ in women and men, but how this influences risk prediction and whether a sex-specific approach is required is unclear. We evaluated whether sex influences the predictive ability of cardiac troponin I and T for cardiovascular events in the general population. Methods: High-sensitivity cardiac troponin (hs-cTn) I and T were measured in the Generation Scotland Scottish Family Health Study of randomly selected volunteers drawn from the general population between 2006 and 2011. Cox-regression models evaluated associations between hs-cTnI and hs-cTnT and the primary outcome of cardiovascular death, myocardial infarction, or stroke. Results: In 19 501 (58% women, mean age 47 years) participants, the primary outcome occurred in 2.7% (306/11 375) of women and 5.1% (411/8126) of men during the median follow-up period of 7.9 (IQR, 7.1–9.2) years. Cardiac troponin I and T concentrations were lower in women than men ( P < 0.001 for both), and both were more strongly associated with cardiovascular events in women than men. For example, at a hs-cTnI concentration of 10 ng/L, the hazard ratio relative to the limit of blank was 9.7 (95% CI 7.6–12.4) and 5.6 (95% CI 4.7–6.6) for women and men, respectively. The hazard ratio for hs-cTnT at a concentration of 10 ng/L relative to the limit of blank was 3.7 (95% CI 3.1–4.3) and 2.2 (95% CI 2.0–2.5) for women and men, respectively. Conclusions: Cardiac troponin concentrations differ in women and men and are stronger predictors of cardiovascular events in women. Sex-specific approaches are required to provide equivalent risk prediction.